2022
DOI: 10.1007/s11258-022-01257-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in climate and seedling establishment at a dry tropical treeline

Abstract: In some internal valleys of the northern Andes, precipitation at treeline elevation is seasonal, with one or two dry periods that could exert a strong control on tree seedling survival. However, little is known about (1) the severity of the dry periods, due to a lack of climate data, or (2) the effect of drought on tree seedling demographic dynamics and how this is modulated by local plant interactions in these tropical-alpine ecosystems. We studied annual precipitation variation and seedling demography and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…(2023) reported that the genetic health of a tropical montane tree species in Mexico is threatened by human activity and climate change. Research on treeline expansion has also shown that dry conditions in the boundary between TMF and páramo in the Venezuelan Andes support a seedling bank, but with slow growth (Ramírez et al ., 2022); and some species may need treatment, such as scarification, to increase germination rates (Liyanage et al ., 2022). Thus, understanding the genetic adaptations and environmental influence of seeds and seedlings is crucial for conservation efforts.…”
Section: Recent Workmentioning
confidence: 99%
“…(2023) reported that the genetic health of a tropical montane tree species in Mexico is threatened by human activity and climate change. Research on treeline expansion has also shown that dry conditions in the boundary between TMF and páramo in the Venezuelan Andes support a seedling bank, but with slow growth (Ramírez et al ., 2022); and some species may need treatment, such as scarification, to increase germination rates (Liyanage et al ., 2022). Thus, understanding the genetic adaptations and environmental influence of seeds and seedlings is crucial for conservation efforts.…”
Section: Recent Workmentioning
confidence: 99%